Coding behavior of authentication code on the internet. - Lin, Shu-Chiung; Yen, David C.; Chen, Patrick S.; Lin, Wei-Kuo (Computers in Human Behavior, 2013)
Highlights: [•] Use of authentication codes may be the troublesome part of information management. [•] Using accounts and passwords is an indispensable part of coding management. [•] Online users usually create self-constructed rules to manage authentication code. [•] Educate online users to build a healthy attitude toward using accounts and passwords. [•] Major suspects of authentication code usurpation lie among closest friends and relatives.